2023
DOI: 10.1002/biof.2009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic potential of naturally occurring piceatannol in non‐communicable diseases

Himanshu Gandhi,
Shikha Mahant,
Abhishek Kumar Sharma
et al.

Abstract: Piceatannol is a naturally occurring hydroxylated resveratrol analogue that can be found in a variety of fruits and vegetables. It has been documented to have a wide range of beneficial effects, including anti‐inflammatory, antioxidant, anti‐aging, anti‐allergic, antidiabetic, neuroprotective, cardioprotective, and chemopreventive properties. Piceatannol has significantly higher antioxidant activity than resveratrol. Piceatannol has been shown in preclinical studies to have the ability to inhibit or reduce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Molecules 2024, 29, x FOR PEER REVIEW 3 of 17 lab have shown that CYP1B1, an enzyme that has oestradiol as its natural substrate, also catalyses the conversion of resveratrol into piceatannol (E)-3, 4,3′,5′-tetrahydroxy stilbene [28]. Piceatannol differs from resveratrol by having one additional aromatic hydroxyl group, thus creating the catechol motif that is commonly found in kinase inhibitors [29,30]. The pharmacokinetic profile of resveratrol is rather poor.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules 2024, 29, x FOR PEER REVIEW 3 of 17 lab have shown that CYP1B1, an enzyme that has oestradiol as its natural substrate, also catalyses the conversion of resveratrol into piceatannol (E)-3, 4,3′,5′-tetrahydroxy stilbene [28]. Piceatannol differs from resveratrol by having one additional aromatic hydroxyl group, thus creating the catechol motif that is commonly found in kinase inhibitors [29,30]. The pharmacokinetic profile of resveratrol is rather poor.…”
Section: Introductionmentioning
confidence: 99%